Protective Effects of HDL Against Ischemia/Reperfusion Injury - Gomaraschi, Monica; Calabresi, Laura; Franceschini, Guido (Frontiers in Pharmacology, 2016)
Several lines of evidence suggest that, besides being a strong independent predictor of the occurrence of primary coronary events, a low plasma HDL cholesterol level is also associated with short- and long-term unfavorable prognosis in patients who have recovered from a myocardial infarction, suggesting a direct detrimental effect of low HDL on post-ischemic myocardial function. Experiments performed in ex vivo and in vivo models of myocardial ischemia/reperfusion (I/R) injury have clearly shown that HDL are able to preserve cardiac function when given before ischemia or at reperfusion; the protective effects of HDL against I/R injury have been also confirmed in other tissues and organs, as brain and hind limb. HDL were shown to act on coronary endothelial cells, by limiting the increase of endothelium permeability and promoting vasodilation and neoangiogenesis, on white blood cells, by reducing their infiltration into the ischemic tissue and the release of pro-inflammatory and matrix-degrading molecules, and on cardiomyocytes, by preventing the activation of the apoptotic cascade. Synthetic HDL retain the cardioprotective activity of plasma-derived HDL and may become a useful adjunctive therapy to improve clinical outcomes in patients with acute coronary syndromes or undergoing coronary procedures.